Congratulations to the anniversary. Klimov Oleg Yurevich – 70 - Hakob, (History and Culture, 2023)
The article is devoted to the prominent representative of the St. Petersburg school of antiquity Dr. Sci. (History), Professor O.Yu. Klimov. The scientist has played a big role in the study of the history of Asia Minor, in particular, in the study of the history of the kingdom of Pergamon. These questions are directly related to the key problems of the history of ancient Armenia. At the same time, works of O. Yu. Klimov, dedicated to the famous German researcher E. Meyer, are very important.
Keywords: Klimov Oleg Yurevich; antiquarian; history; Pergamon; E. Meyer; E.D. Frolov; St. Petersburg State University; History of Ancient Greece and Rome